Dinamika Dakwah Islam Dalam Menghadapi Tantangan Di Era Digital: Perspektif Nahdlatul Ulama Dan Muhammadiyah - Nadiyah, Nur Rifqah; Muh. Nur Rochim Maksum (AT-TAWASUL, 2024)
The digital era has brought changes to Islamic da'wah, providing various challenges. NU and Muhammadiyah can also have different strategic perspectives and approaches in preaching in the digital era. This research aims to find out what the challenges are for Islamic da'wah in the digital era and what are the strategies of NU and Muhammadiyah in dealing with da'wah in the digital era. The research method is qualitative in the form of a literature study with a descriptive approach. The data collection technique is documentation. The research results show that NU and Muhammadiyah are both responding and innovating in da'wah in the digital era. NU is active on various social media such as Instagram, Twitter, Facebook, YouTube, and da'wah on the NU Online site which is always existing and significant, as well as launching the podcast program "Jagat Da'wah NU". Meanwhile, Muhammadiyah also quickly responded to the digital era with a da'wah strategy, developing sites such as muhammadiyah.or.id and suaramuhammadiyah.id, preaching through TVMu, and being active on Instagram, Twitter, Youtube, Facebook and TikTok with informative and interesting religious content. The main challenges in da'wah in the digital era include the dissemination of information or da'wah content that is hoax or inaccurate, da'wah content must be interesting and creative, da'i need to have competence in da'wah in the digital era to be able to preach effectively, as well as methods of delivering information or Da'wah content needs to be considered, with a concise, concise and informative approach.